Evaluation of large-scale poultry manure-derived biochar for efficient cadmium removal in zinc smelter wastewater - Lee, Jae In; Jang, Su Heon; Kim, Changsup; Kang, Jin Kyu; Lee, Chang Gu; Park, Seong Jik (Journal of Environmental Management, 2024)
Cadmium (Cd), a carcinogen, is released from industrial activities like metal refineries and battery runoff, with significant contamination reported near zinc smelters in Korea. This study addresses the issue using an efficient, economical adsorption process with waste-derived biochar-based adsorbents known for high Cd removal. Poultry manure (PM), typically used as fertilizer, can lead to environmental pollution if mismanaged; therefore, it was pyrolyzed to produce biochar. The resulting poultry manure biochar (PMBC) was produced on a large scale (15 ton/day), demonstrating feasibility for large-scale implementation. The effectiveness of PMBC as an adsorbent for Cd was evaluated using wastewater discharged from a zinc smelter. The Cd adsorption capacity of PMBC (60.39 mg/g) was lower than that (302.0 mg/g) of hen manure biochar produced at a laboratory scale in our previous study but was comparable to other biochars reported in the literature. Response surface methodology analysis indicated that reaction time, dose, and agitation significantly influenced Cd removal by PMBC, whereas pH had a negligible impact. Notable contributions to Cd adsorption include the release of K+ from PMBC and the presence of O-containing functional groups. Under continuous flow conditions with real wastewater, Cd was not detected in the effluent for the initial 8 h, and PMBC sustained a removal efficiency of 40.77% until saturation was reached. The results from wastewater treatment and large-scale biochar production offer valuable insights into the potential of biochar as a medium for addressing environmental issues in real-world applications.
Keywords: Biochar; Cadmium adsorption; Cadmium removal; Cadmium(II); Flow condition; Industrial activities; Industrial wastewaters; Large-scales; Optimisations; Poultry manure; Adsorption; Animals; Cadmium; Charcoal; Manure; Poultry; Wastewater; Water Pollutants, Chemical; Zinc; Adsorption; Cd(II); Flow conditions; Industrial wastewater; Mechanism; Optimization